Quantized output feedback resilient control of uncertain systems under hybrid cyber attacks - Yu, Kun; Chang, Xiao‐Heng (International journal of adaptive control and signal processing, 2022)
Summary This article investigates the output feedback resilient control problem of an uncertain system with two quantized signals under hybrid cyber attacks. First, for uncertain systems, the output signal of the system and the output signal of the controller are quantized once by the quantizers before they are passed to the controller and the system respectively, thus affecting the signal with quantization error terms. At the same time, The adverse effects of hybrid cyber attacks, including denial‐of‐service attacks and deception attacks, are also taken into account during the signaling process. In this article, a guaranteed cost resilient controller design method is proposed for the above situation so that the closed‐loop system can be guaranteed to be stable or to meet the given performance index. In addition, by solving the given set of linear matrix inequalities, the design conditions for the relevant parameters required for the resilient controller can be obtained. Finally, the validity of the design method can be verified by simulation.